Knowledge of dental students and professionals about the management of traumatic dental injuries - Marcela Baraúna Magno; Patrícia Nadelman; Matheus Melo Pithon; Lucianne Cople Maia (Universidade Estadual de Campinas, 2019)
Knowledge about the diagnosis and treatment of traumatic dental injuries (TDIs) is extremely important in improving the prognosis of such cases. Aim: To evaluate the knowledge of dental students and professionals about the management of TDIs, and the factors that influence this knowledge, through a literature review. Methods: An electronic search was performed in the PubMed database, with no language or date restrictions. Studies that evaluated the knowledge of dental students or professionals about the management of TDIs were considered eligible. Results: From a total of 1902 retrieved papers, 36 full-texts were assessed for eligibility, and 31 were included in this review. All studies evaluated TDI knowledge through questionnaires; 15 of them only concerned tooth avulsion. In general, knowledge about TDI treatment, both in deciduous and permanent dentition, was considered to be low or moderate. Individual factors (age and gender), professional factors (postgraduate degree, qualification time and place of work), and previous TDI knowledge (attendance frequency, previous education and self-judgment about the knowledge) influenced the knowledge and the frequency of correct answers. Conclusion: Dentistry student and professional knowledge about TDIs is not satisfactory.